Effect of O3 and O3/H2O2 on algae harvesting using chitosan - Pranowo, R.; Lee, D. J.; Liu, J. C.; Chang, J. S. (Water science and technology, 2013)
We examined the effects of pre-oxidation using ozone (O3) and a combination of O3 and hydrogen peroxide (O3/H2O2) on algae suspensions and their harvesting. Inactivation of algae cells, release of intracellular organic matter (IOM), mineralization of extracellular organic matter (EOM), and changes in molecular weight distribution of EOM were found after pre-oxidation. Enhanced separation efficiency of turbidity, dissolved organic carbon (DOC), protein, and polysaccharide using chitosan and polyaluminum chloride (PACl) was found after pre-oxidation, especially when algae cells were subject to O3/H2O2. Chitosan showed higher efficiency than PACl. Judging from the remarkable increase in floc size, it was proposed that released IOM formed complexes with cationic chitosan and resulted in enhanced dual flocculation and facilitated algae separation.